Cross-cultural adaptation and reliability of pediatric sleep questionnaire in assessment of sleep-disordered breathing in the Malay speaking population. - A L, Hasniah; Ab Rahman, Jamalludin; A W, Norrashidah; M Z, Norzila; K, Asiah; A, Rus Anida; Abdullah, Ahmad Fadzil; Z, Ramli; H, Samsinah (Zhejiang University * School of Medicine Children's Hospital, 2012)
Both English and Malay UM PSQ have acceptable psychometric measurement properties as screening tools to assess SDB in the Malay speaking population.